THE USE OF THE TALKING CHIP TECHNIQUE TO IMPROVE THE SPEAKING SKILLS OF EIGHTH-GRADE STUDENTS AT SMPI DARUDDA’WAH PUNGGUR - Indra Gunawan; Nizarrahmadi (Politeknik Negeri Jakarta, 2025)
This study aimed to improve the speaking performance of eighth-grade students at SMPI Darudda’wah Punggur by applying the Talking Chip technique. Employing a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, the study was conducted in two cycles with 20 participating students. Data collection methods included observation, oral assessments, documentation, and audio recordings. Pre-survey findings revealed that only 20% of students met the Minimum Mastery Criteria (KKM) score of 74. Implementation of the Talking Chip strategy led to marked improvements in fluency, pronunciation, grammar, vocabulary, and interactional strategies. By the conclusion of the second cycle, the mastery rate exceeded 85%. The findings confirm that the Talking Chip technique is effective in promoting active participation, increasing motivation, and ensuring equal speaking opportunities for all learners.